Molecular and biological characterization of tobacco mild green mosaic virus from Petunia (Petunia × hybrida) in Brazil - Vinicius Henrique Bello; Lorenna Leal Pires; Gleice Rafaela Renunza Pires; Gustavo Verruma Bernardi; Pedro Luis Ramos-González; Renato Barbosa Salaroli; Elliot Watanabe Kitajima (Scientia Agricola)
ABSTRACT An isolate of the tobamovirus tobacco mild green mosaic virus (TMGMV), Tobamovirus mititessellati, was found naturally infecting petunia (Petunia × hybrida) cv. Pinstripe, causing reduced leaf size, mottling, and color breaking of flowers, in an experimental field at Piracicaba, São Paulo state, Brazil. TMGMV was identified by virion morphology, cytopathology, transmission experiments, and molecular assays. The entire nucleotide sequence of this petunia isolate of TMGMV (TMGMV-Pet) was obtained and demonstrated, in essence, to be similar to previously analyzed isolates. One hundred and twenty plant species were assayed by mechanical transmission, and 35 of them from nine families, both previously reported and unreported species, were shown to be experimentally susceptible to TMGMV-Pet. On the other hand, certain species, among 85 unsusceptible hosts for TMGMV-Pet, known to be susceptible to TMGMV, failed to be infected. Cytopathological studies on naturally and experimentally infected host plants revealed that virions of TMGMV-Pet produced para-crystalline aggregates, but not angular arrays, which are considered characteristic of TMGMV. As previously described, thin sections revealed the presence of pseudo-virions in the stroma of chloroplasts in TMGMV-Pet-infected tobacco (Nicotiana tabacum), and, additionally, in other hosts such as N. clevelandii, N. megalosyphon, and petunia indicating that this process is not restricted to tobacco.